Strategi Dakwah Kiai Abdul Ghofur di Era Milenial - Ainur Rofiq (Mudir : Jurnal Manajemen Pendidikan, 2020)
Religious proselytizing contains interpretation as a invitation activity, even in verbal, transcription, behavior or others, which is done mindfully and by plan in an effort influencing other people individually or by team in order to appear an understanding, awareness, comprehension attitude, and also religion teaching experience for themselves as a massage, delivered to them without any enforcement substances. Religion proselytizing is a process without interruption, that is handled by its developer to change the objects of religious proselytizing, in order they want to join in Allah’s theory in phases into Islamic personality. Besides as a missionary/Dai teacher, scientific, and art fighter, he is also a success entrepreneur. Because of the minimum estimate of pesantren from government, Pon. Pes, Sunan Drajat can stand alone to finance everyday life of a hundred Islamic students freely by working some companies under a power of Islamic Boarding School Lamongan, so that by these companies, many consumers, connecting with the companies, invite their children and neighbor to stay in pondok, study, and look for science in Pondok Pesantren Sunan Drajat. Because his struggle is using social media, as like PERSADA radio, TV, internet, and others. In giving the religious proselytizing in the center societies of Banjarwati village, Kiai Abdul Ghofur refers to religious proselytizing methods bi al Hikmahand Mauizatu al-Hasanah . These used methods give religious proselytizing activity characteristic, which he does pass through teaching kitab kuning, extracurricular lecture, and also advices.